FATHERS' PERCEPTIONS OF EDUCATION, CHILDREN'S EDUCATIONAL FACILITIES, CHILD-PARENT COMMUNICATION, AND ADOLESCENTS' SCHOOL CONTINUATION MOTIVATION IN FAMILIES OF CIRCULAR MIGRANT WORKERS - Adhelya Putri; Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Children who come from families of circular migrant workers with separated parents and children have their own challenges in order to continue to be motivated to continue their education. This study aims to analyze the influence of father's perception of children's education, provision of educational facilities, and child-parent communication on adolescents' motivation to continue school in families of circular migrant workers. This research is a quantitative study with a non-probability sampling method through snowball sampling technique. The number of participants in this study were 40 children and 40 fathers. The results showed that the higher the father's last education, the more motivation for children to continue their education. Meanwhile, the greater the number of children can reduce the motivation to continue education. Other results showed that fathers' perceptions were in the moderate category. Provision of children's education facilities and child-mother communication have a significant positive relationship and effect on increasing motivation to continue schooling. Motivation to continue school in both dimensions is in the low category, namely intrinsic motivation (40%) and extrinsic motivation (70%). Future research is expected to examine perceptions of children's education through the perspective of migrant worker family mothers.